Potential regulatory genes of light induced anthocyanin accumulation in sweet cherry identified by combining transcriptome and metabolome analysis - Zhang, Yao; Chen, Chaoqun; Cui, Yiling; Du, Qinsong; Tang, Wenjing; Yang, Wenlong; Kou, Guanqiong; Tang, Wanjia; Chen, Hongxu; Gong, Ronggao (Frontiers in Plant Science, 2023)
Anthocyanins exist widely in various plant tissues and organs, and they play an important role in plant reproduction, disease resistance, stress resistance, and protection of human vision. Most fruit anthocyanins can be induced to accumulate by light. Here, we shaded the "Hong Deng" sweet cherry to explore the role of light in anthocyanin accumulation. The total anthocyanin content of the fruit and two of its anthocyanin components were significantly reduced after the shading. Transcriptome and metabolomics analysis revealed that PAL, 4CL, HCT, ANS and other structural genes of the anthocyanin pathway and cyanidin 3-O-glucoside, cyanidin 3-O-rutinoside, and other metabolites were significantly affected by shading. Weighted total gene network analysis and correlation analysis showed that the upstream and middle structural genes 4CL2, 4CL3, and HCT2 of anthocyanin biosynthesis may be the key genes affecting the anthocyanin content variations in fruits after light shading. Their expression levels may be regulated by transcription factors such as LBD, ERF4, NAC2, NAC3, FKF1, LHY, RVE1, and RVE2. This study revealed for the first time the possible role of LBD, FKF1, and other transcription factors in the light-induced anthocyanin accumulation of sweet cherry, thereby laying a preliminary foundation for further research on the role of light in anthocyanin accumulation of deep red fruit varieties and the genetic breeding of sweet cherry.